2017
DOI: 10.1007/s10456-017-9541-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of vasculature in bone development, regeneration and proper systemic functioning

Abstract: Bone is a richly vascularized connective tissue. As the main source of oxygen, nutrients, hormones, neurotransmitters and growth factors delivered to the bone cells, vasculature is indispensable for appropriate bone development, regeneration and remodeling. Bone vasculature also orchestrates the process of hematopoiesis. Blood supply to the skeletal system is provided by the networks of arteries and arterioles, having distinct molecular characteristics and localizations within the bone structures. Blood vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
283
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(311 citation statements)
references
References 75 publications
(93 reference statements)
4
283
0
3
Order By: Relevance
“…Therefore, the significant decrease in the Wnt4 level served as a genetic indicator of tibia deformation and resorption. It is known that the growth and development of the bone cannot be separated from the nutritional support of the blood [14]. In summary, the results of our systemic study comparing clinical, pathological and genetic indicators in self-healing tibial dyschondroplasia chickens and normal…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, the significant decrease in the Wnt4 level served as a genetic indicator of tibia deformation and resorption. It is known that the growth and development of the bone cannot be separated from the nutritional support of the blood [14]. In summary, the results of our systemic study comparing clinical, pathological and genetic indicators in self-healing tibial dyschondroplasia chickens and normal…”
Section: Discussionmentioning
confidence: 84%
“…In TD, a large amount of the cartilage cell damage is due to the apoptosis process and abnormal protein secretion in cartilage cells, causing a decrease in the cartilage extracellular matrix degradation rate, which limits the space for bone deposition [12,13]. Currently, research focuses on increasing the growth rate and feed conversion ratio (FCR) of broilers; consequently, poultry bone disease incidence is also increasing in the broiler industry [5,14,15]. It is reported that the chicken muscle tissue and bone growth and development destroy the original balance and are also a reason for the leg deformities in chicken [16].…”
Section: Introductionmentioning
confidence: 99%
“…fluid shear and cyclic stretch) rather than abluminal stimulation of the vessel network itself [1]. Abluminal forces are particularly relevant to load-bearing tissues such as bone, and it is well established that angiogenesis and osteogenesis are intimately linked in both development and healing [2, 3]. Additionally, previous work in vivo showed that functional loading has a potent time-dependent influence on vascular growth during segmental bone defect healing; early loading impaired vessel growth, whereas delayed loading enhanced vascular growth [4].…”
Section: Introductionmentioning
confidence: 99%
“…During bone endochondral and intramembranous ossification, regeneration and remodeling, the vasculature plays an important role [45]. Ten to fifteen percent of total cardiac output goes to skeletal system [46].…”
Section: Vasculature Involved In Bone Formation and Bone Remodelingmentioning
confidence: 99%